A novel volatile organic compound cryogenic recovery system with cold energy storage. (February 2021) - Gao, Xinyue; Song, Danyang; Ling, Xiang; Li, Xin
Highlights: l A novel VOC cryogenic recovery system with cold energy storage was designed. l The system can deal with exhaust gas discharged intermittently or under variable conditions. l The system can use valley power for large-scale cold storage, providing cooling capacity for system operation at peak power consumption. l The dynamic behaviors of the system under external disturbances were studied. Abstract: For recovery of volatile organic compounds (VOCs) from exhaust gas, the traditional condensation method cannot meet existing emission standards because the refrigeration is insufficient, and the operating cost is high when dealing with exhaust gas discharged intermittently or under variable conditions. To overcome these problems, a novel VOC cryogenic recovery system with cold energy storage has been designed by combining turbine expansion refrigeration technology with cold energy storage technology. Intermittently discharged oil gas was selected as the treatment object, and steady-state and dynamic simulation of the system was carried out by HYSYS. The steady-state simulation results show that the non-methane total hydrocarbon emission concentration (NMHC) after treatment is 57.54 mg/Nm 3 and the comprehensive recovery rate of oil gas is as high as 99.99%, which can meet the current emission standards. In addition, due to the application of cold energy storage technology, the system can use valley power for large-scale cold storage, providing cooling capacity for system operation at peak power consumption, which can reduce the operating cost. Finally, the dynamic simulation results show that the system has good dynamic characteristics. When the feed condition of the system is disturbed, the system can recover stability, and the overall performance parameters are less disturbed, which proves that the system can deal effectively with off-design VOC exhaust gas. The conclusions of this paper are of great significance to industrial applications involving VOC exhaust gas with variable conditions and intermittent emission. Graphical abstract: Image, graphical abstract